Pelatihan Website dan Aplikasi SIKAPAL bagi Panglima Laot Guna Meningkatkan Keefektifan Pelaporan Illegal Fishing - Afriandi, Fadli; Rahmawati, Rahmawati; Ridho, Abdurrahman; Auliya, Resti; Hakimi, Akhramil (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Aceh Singkil has abundant marine fisheries resources, but illegal fishing activities that often occur for profit can damage the marine ecosystem and reduce the welfare of traditional fishermen. In Aceh Singkil there is the Panglima Laot traditional institution tasked with maintaining maritime security, but this task is not in line with the reality on the ground. To assist Panglima Laot in handling illegal fishing in Aceh Singkil, the Panglima Laot website and the SIKAPAL application are used to report illegal fishing activities. This method of community service is demonstration and direct practice. In carrying out this service there are five stages, namely planning, preparation, delivery of technical material, practicum and evaluation. With this activity, Panglima Laot Aceh Singkil has a traditional institutional platform which includes a feature for reporting illegal fishing activities. The SIKAPAL website and application also contribute to providing knowledge and information to the fishing community.